2021
DOI: 10.3389/fpsyg.2021.788756
|View full text |Cite
|
Sign up to set email alerts
|

Chinese English as a Foreign Language Teachers’ Self-Efficacy and Psychological Well-Being as Predictors of Their Work Engagement

Abstract: Work engagement is widely acknowledged as an influential element in teachers’ professional success; thus, remarkable attention has been paid to the physical and psychological predictors of this construct. Yet, the antecedents of English as a foreign language (EFL) teachers’ work engagement have rarely been studied. To narrow the existing gap, the current inquiry aimed to delve into the psychological determinants of teacher work engagement by scrutinizing the role of psychological well-being and self-efficacy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 79 publications
(125 reference statements)
1
18
0
Order By: Relevance
“…A similar pattern of results was obtained by Lipscomb et al (2021) in that self-efficacious educators with positive attitudes toward their capabilities in employing operational methodologies, involving learners have a great tendency to involve in the instruction. This study is also consistent with Kong (2021) , who mentioned that teachers with higher levels of self-efficacy can prevail over the teaching difficulties, put more effort into instruction, and have higher levels of grittiness in facing demanding issues. This research proves Granziera and Perera (2019) , who found an inter-relatedness construct between job satisfaction, teacher individual efficacy, and job engagement.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A similar pattern of results was obtained by Lipscomb et al (2021) in that self-efficacious educators with positive attitudes toward their capabilities in employing operational methodologies, involving learners have a great tendency to involve in the instruction. This study is also consistent with Kong (2021) , who mentioned that teachers with higher levels of self-efficacy can prevail over the teaching difficulties, put more effort into instruction, and have higher levels of grittiness in facing demanding issues. This research proves Granziera and Perera (2019) , who found an inter-relatedness construct between job satisfaction, teacher individual efficacy, and job engagement.…”
Section: Discussionsupporting
confidence: 91%
“… Kong (2021) , on the other hand, found a direct correlation between teacher engagement and self-efficacy. His study showed that Chinese EFL educators’ job involvement is significantly influenced by their well-being and efficacy.…”
Section: Review Of Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…Given that language teaching is among the occupations with the highest degrees of stress, teachers bear many negative emotions and stress in their work environment ( Mercer and Gregersen, 2020 ). As such, the investigation of EFL teachers’ psychological variables has been the subject of significant number of studies recently (e.g., Talbot and Mercer, 2018 ; Kong, 2021 ; Liu et al, 2021 ; Chu and Liu, 2022 ; Liu and Chu, 2022 ). For example, Liu and Chu (2022) carried out a quantitative study to examine the construct of resilience among Chinese EFL teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their cross-cultural study, Greenier et al (2021) figured out that psychological wellbeing was a significant predictor of both Iranian ( N = 255) and British ( N = 108) language teachers’ work engagement. Likewise, Kong (2021) studied 304 Chinese EFL teachers’ work engagement and found that their self-efficacy and psychological wellbeing significantly predicted their dedication to the job.…”
Section: Literature Reviewmentioning
confidence: 99%